STRATEGI KOMUNIKASI PUBLIC RELATIONS HOTEL CLARO MAKASSAR DALAM MEMPERTAHANKAN MINAT PENGUNJUNG D’LIQUID (Fakultas Dakwah dan Komunikasi, 2020)
his research aims to find out the communication strategy of public relations at Claro Makassar Hotel in maintaining the interest of D'Liquid visitors and understanding the supporting and inhibiting factors. This type of research is qualitative descriptive, the informants in this study were four people including the head of the D'Liquid Public Relations team, employees, receptionists and one of the visitors of D'Liquid. The approach used is a qualitative approach. Data analysis techniques in this study include data condensation, data presentation and drawing conclusions or verification. Claro Hotel's Public Relations Communication Strategy in Maintaining the D'liquid Visitor's Interest, namely: conducting promotions, designing new innovations, making partnerships with partners as a form of publication on D'liquid, and providing the best service in creating a sense of comfort for visitors. The results of this study also indicate that there are several supporting factors, namely, the completeness of facilities, attractive promos, sponsors, human resources. Obstacle factor; damage to facilities, misunderstandings between employees and visitors, the search for sponsors in publicizing D'Liquid activities, and delays in the appearance schedule of guest stars. his research aims to find out the communication strategy of public relations at Claro Makassar Hotel in maintaining the interest of D'Liquid visitors and understanding the supporting and inhibiting factors. This type of research is qualitative descriptive, the informants in this study were four people including the head of the D'Liquid Public Relations team, employees, receptionists and one of the visitors of D'Liquid. The approach used is a qualitative approach. Data analysis techniques in this study include data condensation, data presentation and drawing conclusions or verification. Claro Hotel's Public Relations Communication Strategy in Maintaining the D'liquid Visitor's Interest, namely: conducting promotions, designing new innovations, making partnerships with partners as a form of publication on D'liquid, and providing the best service in creating a sense of comfort for visitors. The results of this study also indicate that there are several supporting factors, namely, the completeness of facilities, attractive promos, sponsors, human resources. Obstacle factor; damage to facilities, misunderstandings between employees and visitors, the search for sponsors in publicizing D'Liquid activities, and delays in the appearance schedule of guest stars.